The Influence of Brand Image on Customer Loyalty through Promotion as Intervening Variable on Coffeelabs Shop - Marginingsih, Ria; Mulyati, Sri; Darodjat, Tubagus Achmad; Suasungnern, Sineenat (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
The purpose of this study is to ascertain how promotions affect consumer loyalty at the CoffeeLabs Store, using brand image as a mediating variable. Customers who had bought products from the CoffeeLabs Store constituted the study's population, and 120 responses were gathered using non-probability sampling techniques. The SmartPLS 4.0 tool was utilized to do a Partial Least Square (PLS) analysis of the data. Based on the findings of the hypothesis test, the study's findings show that every hypothesis is accepted. The study's findings indicate that, with brand image acting as a mediating variable, promotions have a favorable and noteworthy impact on consumer loyalty. Keywords: Brand Image; Promotion; Customer Loyalty; Coffee Shop; Marketing